Research on the Modeling and Simulation of Optimal Dynamic Aerial Ammunition Scheduling and Transportation (Xibei Gongye Daxue Xuebao, 2018)
To optimize the aerial ammunition scheduling and transportation, both the synergy among all departments of aerial ammunition support system and uncertain factors, such as traffic and attack situations, are taken into consideration in the model. The traffic and attack situations of roads are quantified as crossing time through the model so that the optimization can be simplified into multi-source shortest path problem. Then the optimal transport path of aerial ammunition and combination of storages can be determined by the improved Floyd-Warshall algorithm. Simulation result shows that the dynamic aerial ammunition scheduling and transportation model proposed in this paper is more suitable than traditional model in changing the decision according to the real-time fighting, so as to provide more reliable guarantee of troops.